(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Purpose. To assess and evaluate cytological changes of conjunctival epithelial cells collected by CIC and relative expression of CD15 before and after 2-month treatment with sodium hyaluronate 0.2% and 0.001% hydrocortisone among patients with dysregulatory inflammatory changes of the conjunctiva in type 2 diabetes mellitus. Methods. We prospectively enrolled 38 T2DM patients (76 eyes). All patients were further divided into two groups: Group I - study group (n=23; 46 eyes); Group II - controls (n=15; 30 eyes). Group I received one drop of sodium hyaluronate 0.2% and 0.001% hydrocortisone (HA/Hydrocortisone); group II – one drop of sodium hyaluronate two times daily for two months, respectively. Results. Relative expression of epithelial CD15 was significantly reduced after the treatment in Group I (p˂0,001) in contrast to Group II (p=0,8726). Absence of CD 15 expression was found in five cases (11%) before treatment and seven cases (15%) after HA/Hydrocortisone administration (p=0,7582). Macrophage infiltration was observed in 28% of participants upon baseline examination and it completely disappeared after treatment with HA/Hydrocortisone. These findings show that HA/hydrocortisone drops should be considered as an effective treatment for patients with dysregulated parainflammation of the conjunctiva. Conclusions. Treatment with hyaluronate/hydrocortisone eye drops showed a statistically significant improvement of conjunctival cytology and functional tests: lipid layer thickness (LLT), tear breakup time (TBUT), meibomian gland loss (MGL) along with reduction of relative expression of epithelial CD15 among T2DM patients.